2000
DOI: 10.1034/j.1399-3003.2000.01512.x
|View full text |Cite
|
Sign up to set email alerts
|

Airway inflammation following exposure to diesel exhaust: a study of time kinetics using induced sputum

Abstract: The adverse health effects of particulate matter pollution are of increasing concern. In a recent bronchoscopic study in healthy volunteers, pronounced airway inflammation was detected following exposure to diesel exhaust (DE). The present study was conducted in order to evaluate the time kinetics of the inflammatory response following exposure to DE using induced sputum from healthy volunteers.Fifteen healthy nonsmoking volunteers were exposed to DE particles with a 50% cut-off aerodynamic diameter of 10 mm 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
84
2
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(92 citation statements)
references
References 33 publications
(28 reference statements)
4
84
2
2
Order By: Relevance
“…This suggests recruitment of granulocytes into the airway and is consistent with numerous previous studies in both animals [42][43][44][45][46] and humans [7,[9][10][11], which have shown increased granulocyte counts, most commonly neutrophilia, in bronchoalveolar lavage and induced sputum samples following exposure to particulate matter. An increase in the number of macrophages in induced sputum was not found in the present study, which suggests that the predominant inflammatory response in the lung with acute wood smoke exposure is neutrophilic in nature.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This suggests recruitment of granulocytes into the airway and is consistent with numerous previous studies in both animals [42][43][44][45][46] and humans [7,[9][10][11], which have shown increased granulocyte counts, most commonly neutrophilia, in bronchoalveolar lavage and induced sputum samples following exposure to particulate matter. An increase in the number of macrophages in induced sputum was not found in the present study, which suggests that the predominant inflammatory response in the lung with acute wood smoke exposure is neutrophilic in nature.…”
Section: Discussionsupporting
confidence: 92%
“…Numerous epidemiological studies have documented a detrimental relationship between exposure to particulate matter in urban air pollution and cardiopulmonary morbidity and mortality with both short-and long-term exposure [1][2][3][4][5]. Although the mechanism by which exposure to particles in urban air induces adverse cardiopulmonary effects remains unclear, several studies from the present authors' laboratory and others support a mechanism in which exposure to fine particles promotes inflammation in the lung [6][7][8][9][10][11] via activation of alveolar macrophages and lung epithelial cells [12][13][14][15][16]. Such exposure is also associated with a systemic inflammatory response [17][18][19][20], which in turn is associated with an increased presence of several cytokines (interleukin (IL)-6, IL-1b) in the bloodstream [21] as well as increased production and release of polymorphonuclear leukocytes (PMN) and monocytes from the bone marrow [17][18][19][20].…”
mentioning
confidence: 54%
“…Studies of induced sputum have also been used to evaluate DE effects on the human airways [32]. Sixteen healthy nonsmoking subjects were exposed to air and DE at a particle concentration of 300 mg .…”
Section: Human Subjectsmentioning
confidence: 99%
“…During the last decade, several epidemiological studies have provided convincing evidence for an association between ambient levels of particulate matter and various health outcome indices, including respiratory symptoms [1], impaired lung function [2], exacerbations of asthma [3,4], emergency room visits [1,5], and an increased risk of respiratory illness in children [6]. Importantly, several studies have suggested that individuals with pre-existing respiratory disease such as asthma are more sensitive to elevated ground levels of particulate matter (PM) pollution as compared to healthy subjects [7,8].…”
mentioning
confidence: 99%